Visual Field Dysfunctions in Warfighters During Different Stages Following Blast and Nonblast mTBI. Issue 2 (1st February 2015) - Walsh, David V.; Capó-Aponte, José E.; Jorgensen-Wagers, Kendra; Temme, Leonard A.; Goodrich, Gregory; Sosa, Josue; Riggs, Daniel W.
ABSTRACT: Objectives: Traumatic brain injury (TBI) is the leading injury coming out of the past decades' two major military conflicts, with mild TBI (mTBI) being the most commonly diagnosed form. The aim of this study was to assess the frequency and types of visual field (VF) defects seen at different testing stages following nonblast and blast-induced mTBI. Methods: A comprehensive retrospective review was performed on 500 electronic health records for military personnel sustaining an mTBI during deployment, of which 166 patients were tested with both confrontation VF and 30-2 Humphrey Matrix Frequency Doubling Technology (FDT) perimetry. Results: Scatter defects (48%) were the most predominantly found deficits in both blast and nonblast mTBI injury mechanisms and over postinjury test time frames. Confrontation VF was shown to be a poor qualitative predictor of VF defect. A profound decrease in VF sensitivity was noted in comparison to previously reported FDT normative data. Finally, a significant trend of decreasing VF defects was seen over time, indicating the potential usage of FDT as a visual biomarker for monitoring mTBI recovery. Conclusions: The findings of this study highlight the importance of performing threshold perimeter testing in those who have suffered an mTBI or concussion-like event.